The fire - Patterson, James, 1947- (Patterson, James, 1947- Witch & wizard novels., 2011)
Whit and Wisty Allgood have led the resistance against a totalitarian regime that has banned all forms of creativity and executed their parents, but even the growing strength of the siblings' magic has not been able to stop the evil dictator, and they must somehow prepare for an imminent showdown.